Study on grinding-chemical machining of Al7075. (17th October 2019) - Azizi, Abdolhamid; Bahrami, Pooya
Chemical machining (CHM) uses a chemical etchant to remove material from the machining zone. Two of the downsides for this method are time-consuming and low surface quality. Wheel loading and surface burning are also two of the major problem in soft material grinding. By combining the chemical machining and grinding, we introduce a mechano-chemical hybrid machining in which the described problems are resolved. The reason for the prominence of this machining method is demonstrated from two points of view; the first one is machining efficiency and the second one is surface quality. In comparison with chemical machining, the surface roughness (Ra) decreased on average by 100% moreover, material removal rate was ameliorated 600% and a burr-free surface was machined. In the second step, due to pre-machining conducted by chemical etching, the priority of the hybrid process compared to grinding is proved by taking in to account the wheel loading, grinding ratio and surface quality.